Small Molecule Interactome Mapping by Photo‐Affinity Labeling (SIM‐PAL) to Identify Binding Sites of Small Molecules on a Proteome‐Wide Scale. Issue 4 (3rd October 2019) - Flaxman, Hope A.; Miyamoto, David K.; Woo, Christina M.
Abstract: Identification and characterization of small molecule–protein interactions is critical to understanding the mechanism of action of bioactive small molecules. Photo‐affinity labeling (PAL) enables the capture of noncovalent interactions for enrichment and unbiased analysis by mass spectrometry (MS). Quantitative proteomics of the enriched proteome reveals potential interactions, and MS characterization of binding sites provides validation and structural insight into the interactions. Here, we describe the identification of the protein targets and binding sites of a small molecule using small molecule interactome mapping by PAL (SIM‐PAL). Cells are exposed to a diazirine‐alkyne‐functionalized small molecule, and binding interactions are covalently captured upon UV irradiation. An isotopically coded, acid‐cleavable biotin azide handle is attached to the conjugated proteins using copper‐catalyzed azide‐alkyne cycloaddition. Biotin‐labeled proteins are enriched for on‐bead digestion and quantitative proteomics. Acid cleavage of the handle releases the bead‐bound conjugated peptides for MS analysis and isotope‐directed assignment of the binding site. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Generation of a small molecule–conjugated protein sample following treatment of live cells Alternate Protocol : Generation of a small molecule–conjugated protein sample following treatment of cell lysate Basic Protocol 2 : Copper‐catalyzed azide‐alkyne cycloaddition functionalization and enrichment of labeled peptides Support Protocol 1 : Synthesis of acid‐cleavable, isotopically coded biotin picolyl azide handle Support Protocol 2 : Monitoring enrichment by immunoblotting Basic Protocol 3 : Mass spectrometry analysis to identify interacting proteins and conjugation sites